Achieve control: a pragmatic clinical trial of insulin glargine 300 U/mL versus other basal insulins in insulin-naïve patients with type 2 diabetes. Issue 8 (16th November 2016) - Oster, Gerry; Sullivan, Sean D.; Dalal, Mehul R.; Kazemi, Mahmood R.; Rojeski, Maria; Wysham, Carol H.; Sung, Jennifer; Johnstone, Bryan; Cali, Anna M.G.; Wei, L.J.; Traylor, Louise; Anhalt, Henry; et al.
ABSTRACT: Objective : This study aims to compare the effectiveness of insulin glargine 300 U/mL (Gla-300) with its accompanying patient support program with that of other basal insulin and available patient support programs in patients with type 2 diabetes (T2D) in a real-world setting in terms of achieving HEDIS (Healthcare Effectiveness Data and Information Set) individualized glycemic targets without documented symptomatic hypoglycemia. Methods : Achieve Control is a US-based, multicenter, randomized, open-label, active-controlled, parallel group pragmatic Phase IV trial in insulin-naïve patients with T2D uncontrolled on ≥2 oral antidiabetes drugs (OAD) and/or glucagon-like peptide-1 receptor antagonists (GLP-1 RA). Inclusion criteria include a diagnosis of T2D, age ≥18 years, and glycated hemoglobin (HbA1c) between 8.0% and 11.0%. Patients will be assigned to either the Gla-300 or other basal insulin group. The primary end point is the proportion of patients achieving HEDIS HbA1c targets (<8.0% [64 mmol/mol] in patients with comorbidities or aged ≥65 years; <7.0% [58 mmol/mol] in all other patients) without occurrence of symptomatic hypoglycemia (blood glucose ≤70 mg/dL) from baseline to 6 months. Secondary end points include rates of documented symptomatic nocturnal hypoglycemia and severe hypoglycemia; change from baseline in HbA1c, fasting glucose, and body weight; treatment persistence; patient-reported outcomes; and healthcare resource utilization. Planned enrollment is 3270 patients across approximately 400 clinical sites. Conclusion : Pragmatic clinical trials offer the potential to assess comparative effectiveness in broadly based patient populations receiving care (with or without a corresponding educational support program) in real-world clinical settings. The results of Achieve Control should elucidate the benefits of management of T2D with Gla-300 versus other basal insulins in terms of patient outcomes, experiences, and perceptions, and its impact on healthcare resource utilization and cost. Clinical trial registration :www.clinicaltrials.gov identifier is NCT02451137.